PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA KELAS III - Fauziah, Anna; Refianti, Rani; Baharudin, Baharudin; Maharani, Dessy (LP4MK STKIP PGRI Lubuklinggau, 2024)
This research aims to find out whether the Problem based learning model assisted by poster media can improve elementary school students' Mathematics learning outcomes. The research was carried out at SD Negeri 41 Lubuklinggau. This type of research is classroom action research. Data collection techniques are carried out using tests, observation and documentation. The data analysis techniques used are qualitative descriptive and quantitative descriptive. This research consists of 3 cycles with research procedures using the Problem based learning model which includes planning, implementing actions, observing and reflecting. The results of the research show that there has been an increase in Mathematics learning outcomes for class III students at SD Negeri 41 Lubuklinggau. In cycle I, students obtained an average pre-test score of 57,73 and post-test 71,47. Cycle 2 average value of pre-test 64.09 and post-test 77,.45. Cycle 3 average value of pre-test 65,73 and post-test 88,09. From the research results, it was concluded that Problem Based Learning can improve elementary school students' Mathematics learning outcomes.